Race, immigration, and homicide in contemporary Europe and the United States: an urban comparison - Martínez, Ramiro (Crime, law and social change, 2015)
In this paper we ask a key question: Do immigrants contribute a disproportionate amount of crime beyond what we would expect from native-born populations? We start with a description of the immigration and homicide literature in the United States and Europe and transition into a description of lessons learned from this topic in the United States. Specifically, we compare the level of immigration to white, black, and Latino homicide rates between 1985 and 2009. We compare and contrast racial/ethnic/immigrant group specific homicide rates in the cities of Miami and San Diego from 1980 through 2000. We do so since both cities are major entry points into the United States. We compare these findings to European countries, because there are some similarities on immigration into the United States and Europe and, by extension, the study of immigration and violence. In many ways, the study of urban immigration and homicide in the United States is relevant to the study of urban immigration and homicide in Europe. Many of the topics discussed in this paper are likely to be faced by European countries in the future and our hope is that findings from the United States are useful in other contexts.